Histone methyltransferase SUV39H1 participates in host defense by methylating mycobacterial histone‐like protein HupB - Yaseen, Imtiyaz (EMBO J, 2017)
Host cell defense against an invading pathogen depends upon various multifactorial mechanisms, several of which remain undiscovered. Here, we report a novel defense mechanism against mycobacterial infection that utilizes the histone methyltransferase, SUV39H1. Normally, a part of the host chromatin, SUV39H1, was also found to be associated with the mycobacterial bacilli during infection. Its binding to bacilli was accompanied by trimethylation of the mycobacterial histone‐like protein, HupB, which in turn reduced the cell adhesion capability of the bacilli. Importantly, SUV39H1‐mediated methylation of HupB reduced the mycobacterial survival inside the host cell. This was also true in mice infection experiments. In addition, the ability of mycobacteria to form biofilms, a survival strategy of the bacteria dependent upon cell–cell adhesion, was dramatically reduced in the presence of SUV39H1. Thus, this novel defense mechanism against mycobacteria represents a surrogate function of the epigenetic modulator, SUV39H1, and operates by interfering with their cell–cell adhesion ability.